Recovery of silver from photographic wastes - Ochotorena, Zenaida (Legaspi) 1935- (s.n.], 1968)
The study described the method of recovering silver from photographic wastes. Results show that a silver nitrate solution obtained from photographic wastes can help address the existing need for silver nitrate in science and high school chemistry classes especially in the rural areas where such chemical may not be available.